Adolescent Suicide And Its Prevention - Jumanova Nasiba Sherbayevna (Academia One Publishing, 2024)
This article provides information on the characteristics of suicide in adolescence and measures to prevent it . Also, the important aspects of carrying out correctional educational work with teenagers with a high level of suicidal risk are covered in detail.
Keywords: Suicide; society; relationships